2012
DOI: 10.4321/s1130-01082012000900005
|View full text |Cite
|
Sign up to set email alerts
|

Low co-existence rates of Lactobacillus spp. and Helicobacter pylori detected in gastric biopsies from patients with gastrointestinal symptoms

Abstract: Background: bacterial diversity of the stomach includes various species. Among them, Helicobacter pylori, a microorganism which has been associated to gastric diseases, is frequently isolated in this habitat. In addition, Lactobacillus spp., a genus including probiotic strains, has also been documented in this habitat. The co-existence of these two species in the stomach of symptomatic patient needs to be elucidated.Aims: our goal was to establish if Lactobacillus spp. and H. pylori co-exist in the stomach muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…pylori strains. [67]. Additionally, the therapies based on long-term or repeated use of antibiotics have also encountered problems on other side effects like alteration of gut microbiota [8].…”
Section: Introductionmentioning
confidence: 99%
“…pylori strains. [67]. Additionally, the therapies based on long-term or repeated use of antibiotics have also encountered problems on other side effects like alteration of gut microbiota [8].…”
Section: Introductionmentioning
confidence: 99%
“…When the inhibition of H. pylori by normal dominant bacteria weakens, the related diseases caused by H. pylori may occur. It was shown that the co-existence of lactobacillus and H. pylori was low in the gastric biopsies of symptomatic patients (7). If the co-existence of both species along with the eradication regimens is reestablished, the growth and the recur-rence of H. pylori may be inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…This strain has also shown, in previous studies, inhibitory ability against H. pylori and probiotic skills (García et al 2009(García et al , 2012. It is for this reason that this systematic study was of particular interest to analyse the production of organic acids and EPS in continuous culture using a chemically defined medium, evaluating the effect of pH and the growth rate on the reaction rates.…”
Section: Discussionmentioning
confidence: 94%
“…In previous studies, this strain has shown important probiotic abilities in vitro, in animal models, and antagonism against pathogenic Helicobacter pylori strains (García et al 2009(García et al , 2012.…”
Section: Introductionmentioning
confidence: 98%